Diviziunea digitală în România – analiză de documente strategice la nivel naţional şi european - Cărtărescu Petrică, Ioana (Calitatea Vieții, 2015)
Even though the European Union is, on average, a world leader when it comes to access to information technology and communications (IT&C) and its citizens’ high level of digital competence, there are great disparities among its member states regarding this issue. Romania is the least digitally developed of the entire EU 28, as it is strongly affected by a new kind of social inequality: the digital divide. Thus, citizens from rural areas, those with lower levels of income and education and members of vulnerable groups have much lower material access to IT&C and digital competences than those who live in urban areas, and those who have higher financial possibilities and education levels. The low level of access of a significant portion of the population constitutes an obstacle in their path to information, education, employment and high competitivity and productivity on the labor market. This state of things eventually has repercussions on the fields of education, employment, social inclusion and the fight against poverty and other important strategic areas on a national level. In an attempt to identify the manner in which the Romanian state envisions its fight against digital divide, in the wider context of the EU recognition of the significant role played by IT&C in the Union’s progress, I have analyzed the provisions of important strategic documents from fields relevant (by topic or by implications) to this type of inequality. The analyzed documents mostly pertain to the national legal framework, but I have also included in my research certain relevant European strategies, through the provisions of which recommendations were made to the member states on the present subject.